PENGARUH PEMBERIAN PUPUK KANDANG SAPI TERHADAP SERAPAN FOSFOR DAN HASIL TANAMAN SAWI PUTIH (Brassica pekinensis) PADA ENTISOLS SIDERA - Fikdalillah, Fikdalillah; Basir, Muhammad; Wahyudi, Imam (AGROTEKBIS, 2016)
This research aimed to determine the effect of Cow Manure on Phospphate Uptake of cabbage in Entisols Sidera. The research used a Randomized Block Design with seven-level treatments ie. S0= control, S1= 10 t ha-1, S2= 20 t ha-1, S3= 30 t ha-1, S4= 40 t ha-1, S5= 50 t ha-1, and S6= 60 tha-1. Each treatment was replicated three times so that there were 21 experimental units. This research used cabbage as an indicator plant with variable observed including soil C-organic, Aldd, soil pH, plant dry weight, soil P-total content, concentration of P tissue and P uptake. Data was analyzed using Regresetion and Corelation. The research result showed that the cow manure significantly affected the cabbage Phospphate uptake and yield of cabbage plant. Key Words : Cabbage, cow manure, Entisols, P Uptake.